Single versus multi‐drug antimicrobial surgical infection prophylaxis for left ventricular assist devices: A systematic review and meta‐analysis. Issue 7 (22nd March 2019) - Patel, Sinal; Choi, Jae Hwan; Moncho Escrivá, Ester; Rizvi, Syed Saif Abbas; Maynes, Elizabeth J.; Samuels, Louis E.; Luc, Jessica G. Y.; Morris, Rohinton J.; Massey, Howard T.; Tchantchaleishvili, Vakhtang; Aburjania, Nana
Abstract: Infection remains the Achilles heel of left ventricular assist device (LVAD) therapy. However, an optimal antimicrobial surgical infection prophylaxis (SIP) regimen has not been established. This study evaluated the efficacy of a single‐drug SIP compared to a multi‐drug SIP on clinical outcomes in patients undergoing continuous‐flow LVAD (CF‐LVAD) and pulsatile LVAD (P‐LVAD) implantation. An electronic search was performed to identify studies in the English literature on SIP regimens in patients undergoing LVAD implantation. Identified articles were assessed for inclusion and exclusion criteria. Fourteen articles with 1, 311 (CF‐LVAD: 888; P‐LVAD: 423) patients were analyzed. Overall, 501 (38.0%) patients received single‐drug SIP, whereas 810 (62.0%) received multi‐drug SIP. Time to infection was comparable between groups. There was no significant difference in overall incidence of LVAD‐specific infections [single‐drug: 18.7% vs. multi‐drug: 24.8%, P = 0.49] including driveline infections [single‐drug: 14.1% vs. multi‐drug: 20.8%, P = 0.37]. Compared to single‐drug SIP, patients who received multi‐drug SIP had a significantly lower survival rate [single‐drug: 90.0% vs. multi‐drug: 76.0%, P = 0.01] and infection‐free survival rate [single‐drug: 88.4% vs. multi‐drug: 77.3%, P = 0.04] at 90 days. However, there were no significant differences in 1‐year survival and 1‐year infection‐free survival between groups. No survival differences were observed in the CF‐LVAD subset as well. This study demonstrated no additional advantage of a multi‐drug compared to a single‐drug regimen for SIP. Although there was a modest advantage in early survival among CF‐LVAD and P‐LVAD patients who received single‐drug SIP, there were no significant differences in the 1‐year survival and 1‐year infection‐free survival.